Using ARIMA models to predict rainfall rates In the Al-Baha region for the period from 1985 to 2014 - OSMAN, AMIRA AHMED (The Arab Journal of Administration, 2024)
The objective of the research is to estimate a model for rainfall forecasting in Al-Baha area due to the importance of rainfall, which is the main source of water in the region. The research used historical data obtained from the Ministry of Water and the General Presidency of Meteorology in the Kingdom. ARIMA model for Box and Jenkins was used to test the research hypotheses, which test for a statistically significant effect of the independent variables namely temperature, relative humidity and wind velocity on the dependent variable. The research found that there was a statistically significant effect of the historical data of the same variable on future values and also found the effect of relative humidity as an independent variable. The research concluded to build a forecasting model that could be used to estimate rainfall in the region to take advantage of decision-making for processing to maintain. The researcher recommended a set of recommendations, the most important of which was the introduction of the model of interest by the competent authorities and recommended the idea of generalizing the research to include all of Saudi Arabia.